Árboles viejos como indicadores de biodiversidad de vertebrados forestales amenazados de la provincia de Salamanca (España) - Núñez, M.; Tarazona, T.; Silla Cortés, Fernando; Delgado Sánchez, Luis (Pirineos, 2016)
Ancient trees abundance has been compared with distribution of threatened forest vertebrate species at the province of Salamanca (Spain). A significant correlation between both parameters has been observed for the following considered species: imperial eagle (Aquila adalberti), black vulture (Aegypus monachus), iberian lynx (Lynx pardinus), red kite (Milvus milvus) and a group of forest bats (Miniopterus schreibersii, Myotis bechsteinii, Myotis emarginatus, Myotis mystacinus, Myotis myotis, Nyctalus lasiopterus, Nyctalus noctula, Rhinolophus euryale, Rhinolophus ferrumequinum y Rhinolophus mehelyi). It has been proved that there is an increase of threatened forest vertebrates biodiversity along with increasing ancient trees density at the municipalities of the province. Therefore, we can deduce that ancient trees density is a good indicator parameter of the conservation status of the forest ecosystem and it is essential for the maintenance of these endangered species. [ES] Se ha comparado la abundancia de árboles viejos en la provincia de Salamanca (España) con la distribución de las especies de vertebrados forestales amenazados presentes, observándose que existe una correlación signi